DEVELOPMENT OF LOCAL TRADE ENTERPRISES USING DIGITAL MARKETING TOOLS (Development Service Industry Management, 2023)
The study emphasizes the relevance of public policy of ensuring local economic development. Emphasis is placed on stimulating the development of trade enterprises, and the possibilities of digital marketing are considered as a tool for the activation of such processes. Based on these principles, the purpose of the study was to improve the methodological and applied principles of the policy of development of trade enterprises at the local level with the use of digital marketing tools.It is shown that trade, as well as digital marketing of domestic trade enterprises at the local level, are currently not very developed and widespread, which proves the existence of a need for further improvement of practices of forming tools for stimulating the development of trade enterprises at the local level, including the use of digitalization tools for such purposes. digital relations and communications. The policy means of stimulating the development of trade enterprises at the local level, as well as the use of digital marketing tools for such purposes, have been determined.It has been established that one of the leading ways to stimulate local economic development in Ukraine is to increase the number and intensify the activity of trade enterprises, which represent a type of economic activity in which investments are not significant, and the time from making a decision to starting a business is not the shortest. Therefore, it is necessary both on the part of local self-government bodies, as well as business and population, to initiate and implement tools aimed at the development of trade entrepreneurship at the local level, especially in remote and rural areas.A promising tool in this sense is digital marketing, which has unlimited potential for fast online communication between businesses and consumers. As shown in the study, communities have a wide range of means of stimulating the development of trade at the local level, but without internal motivation for this on the part of business representatives and the local population, the situation will not change critically positively. Tools should be implemented at different levels and be up-to-date. One of them is digital marketing, which allows trade enterprises to establish high-quality communication with the widest possible audience of users. This is precisely the relevance of the problem of development of trade enterprises at the local level with the use of digital marketing tools.
Keywords: management; enterprise economy; enterprise management; trade business; local economic development; regulation of policy instruments; digital marketing